Using spatial analyses of bearded vulture movements in southern Africa to inform wind turbine placement. Issue 4 (24th June 2015) - Reid, Tim; Krüger, Sonja; Whitfield, D. Philip; Amar, Arjun; Thompson, Des
Summary Concerns over CO2 emissions during energy generation and its effect on climate change have led to increases in the use of renewables, such as wind energy. However, there are also serious environmental concerns over this type of energy production due to its impacts on bats and birds. In southern Africa, bearded vultures have declined by >30% during recent decades. They are now regionally critically endangered with only around 100 active pairs remaining. This species is considered vulnerable to collision with wind turbines which are planned within their southern African range. In this study, we develop habitat use models using data obtained from 21 bearded vultures of different ages fitted with GPS tags from 2009 to 2013. We further refined these models by incorporating flying heights at risk of collision to predict important areas of use that may conflict with wind turbines. Adult and non‐adult bearded vultures mostly used areas with high elevations and steep and rugged topography in the core area; adults tended to use areas in relatively close proximity to their nest sites, whereas non‐adult birds used areas dispersed over the entire species range and were more likely to fly at risk‐height in areas that were less used by adults. Altitudes of fixes of adults and non‐adults showed that they spent 55% and 66% of their time, respectively, at heights that placed them at risk of collision. Examining the locations of two proposed wind farms in relation to our model of predicted 'at risk' usage suggested poor positioning. Indeed, one of these wind farms was located within the 1% of 'worst' (most heavily used) sites for non‐adult bearded vultures suggesting that its current location should be reconsidered to reduce the impact on this vulnerable species. Synthesis and applications. We demonstrate the value of habitat use models for identifying intensively used areas, in order to greatly reduce conflicts with developments such as wind turbines. This tool is operable at the scale of regional and national development plans informed by the habitat use of potentially vulnerable species. Such models should provide important supplementary assessments of site‐specific development proposals.